Identification of COP9 Signalosome Subunit Genes in Bactrocera dorsalis and Functional Analysis of csn3 in Female Fecundity - Zhang, Jing; Zhang, Zhenyu; Zhang, Rui; Zhang, Wenfei; Li, Haozhe; Li, Tianran; Zhang, Hongyu; Zheng, Weiwei (Frontiers in Physiology, 2019)
The COP9 signalosome (CSN) is an evolutionarily conserved multi-subunit complex that plays crucial roles in regulating various biological processes in plants, mammals, and the model insect Drosophila. However, it is poorly studied in non-model insects, whereas its role in fecundity remains unclear. In this study, all nine CSN subunits were identified and characterized in Bactrocera dorsalis, a major invasive agricultural tephritid pest. Each subunit gene, except for csn9x1, encoded a protein containing a PCI/PINT or MPN domain. Phylogenetic analysis revealed that all CSN subunits were individually clustered into a specific branch with their counterparts from other species. All CSN subunit genes were expressed in all detected developmental stages and tissues. Most subunits, except for csn8 and csn9x1, showed the highest expression level in the eggs. Notably, csn3 and csn5 were significantly enriched in mature female adults. Further analysis of csn3 revealed that it was enriched in the ovary and that its ovarian expression level gradually increased with the reproductive development process. RNAi-based knockdown of csn3 in female adults significantly reduced the number of laid eggs. The expression level of EcRB1 and USP, which encode the heterodimer receptors of 20E, and vitellogenin transcripts (Vg1 and Vg2) was suppressed in the fat body of female adults injected with csn3 dsRNA. Decreased level of Vg1 protein was confirmed by means of Western blots. These data indicate that csn3 is involved in female reproduction by regulating 20E signaling and Vg synthesis. Overall, our study may facilitate the development of new strategies for controlling B. dorsalis since it provides insights into the evolution and expression patterns of all CSN subunit genes as well as the critical roles of csn3 in female fecundity.